HIP HOP CABANO: diálogo subjetivo entre culturas de resistencia - ALMEIDA, Caio Bandeira de (2022)
The aim of the present study was to promote an epistemological dialogue between Hip Hop Culture and the Cabanagem movement, verifying if there are any characteristics of Cabanagem in the Hip Hop dancers from Pará today. To this end, a bibliographic review of books, articles, websites was carried out, as well as videos of digital platforms and documentaries were consulted. A questionnaire consisting of 6 open questions was also used, which were answered by 6 dancers and Hip Hop dancers from Belém and Ananindeua by audio messages in a conversation apps. Considering each demonstration according to the place, period and characteristics of the experienced moment, from this study it was possible to understand that, these historically excluded and marginalized peoples, in different times and places, made great demonstrations in favor of their freedom and equality and against authoritarian powers, generating a social and identity construction between them.